2006
DOI: 10.1210/en.2005-1270
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF) Binding Protein-3 Attenuates Prostate Tumor Growth by IGF-Dependent and IGF-Independent Mechanisms

Abstract: IGF binding protein (IGFBP)-3 inhibits cell growth and promotes apoptosis by sequestering free IGFs. In addition IGFBP-3 has IGF-independent, proapoptotic, antiproliferative effects on prostate cancer cells in vitro. Expression of the large T-antigen (Tag) under the long probasin promoter (LPB) in LPB-Tag mice results in prostate tumorigenesis. To investigate the IGF-dependent and IGF-independent effects of IGFBP-3 on prostate tumor growth, we crossed LPB-Tag mice with cytomegalovirus (CMVBP-3) and phosphoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 36 publications
3
60
1
Order By: Relevance
“…Recently, Silha et al (2006) reported a reduction in tumor growth in an IGF-independent IGFBP-3 transgenic model. In our study, we detected no IGF-1 in all sublines by enzyme-linked immunosorbent (ELISA) study.…”
Section: Igfbp-3 As An Invasion-metastasis Suppressor P-l Torng Et Almentioning
confidence: 99%
“…Recently, Silha et al (2006) reported a reduction in tumor growth in an IGF-independent IGFBP-3 transgenic model. In our study, we detected no IGF-1 in all sublines by enzyme-linked immunosorbent (ELISA) study.…”
Section: Igfbp-3 As An Invasion-metastasis Suppressor P-l Torng Et Almentioning
confidence: 99%
“…IGFBP-3 is the most abundant IGFBP in the blood and was also described as having 'IGF-independent' functions since IGFBP-3 was shown to exhibit proapoptotic (Rajah et al 1997, Butt et al 2000, Williams et al 2007) and anti-proliferative functions (Oh et al 1995, Boyle et al 2001, Silha et al 2006, Alami et al 2008, and was described to be a suppressor of angiogenesis (Liu et al 2007). Various studies indicated that IGFBP-3 also acts as an anti-cancer molecule in prostate cancer (Rajah et al 1997, Bhattacharyya et al 2006, Kojima et al 2006, Liu et al 2007, Silha et al 2006, Peng et al 2007. Furthermore, serum IGFBP-3 may also modulate prostate carcinogenesis, although case-control studies correlating IGFBP-3 concentrations in the blood circulation and prostate cancer risk are contradictory (Renehan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo models suggest that the inhibitory effects of IGFBP-3 on cancer were 398 both IGF-dependent and IGF-independent. IGFBP-3 deletion increased the number of metastases in 399 a prostate cancer mouse model (Mehta, et al 2011), whereas overexpression of both wild-type and 400 a mutant IGFBP-3 that does not bind IGFs attenuated prostate cancer growth (Silha, et al 2006). 401…”
mentioning
confidence: 99%